Pengaruh Emotional Intelligence dan Servant Leadership Terhadap Affective Commitment: Job Satisfaction Sebagai Pemediasi - Husna, Nurul; Wahyuningsih, Sri Handari (Jurnal Manajemen Dayasaing, 2025)
This study aims to analyze and test the effect of Emotional Intelligence and Servant Leadership on Affective Commitment with Job Satisfaction as a mediating variable. This study used a sample of 118 respondents from employees of Restoran Traditional “Ayam Ingkung restaurant” in Yogyakarta. The quantitative data analysis technique in this study was SEM with SmartPLS Software version 4.0. The results of this study indicate that (1) emotional intelligence does not have a significant positive effect on affective commitment,(2) servant leadership has a positive and significant effect on affective commitment,(3) job satisfaction has a significant and positive effect on affective commitment,(4) emotional intelligence has a positive and significant effect on job satisfaction,(5) servant leadership has a positive and significant effect on job satisfaction,(6) emotional intelligence has a positive and significant effect on affective commitment through job satisfaction as a mediating variable,(7) servant leadership has a positive and significant effect through job satisfaction as a mediating variable.